Needs Analysis for the Development of a Web-Based Arabic Reading Skills Application Using News Texts in State University of Malang - Wasiatur Rizqiyah; Moh. Khasairi; Achmad Tohe (Al-Zahra : Journal for Islamic and Arabic Studies, 2026)
Arabic reading instruction at the university level faces challenges related to students’ difficulties in understanding Arabic texts, limited digital learning media, and the need for authentic instructional materials. This study aimed to analyze the needs for developing QiraApp, a web-based application for Arabic reading instruction using Arabic news texts. The application is designed to support self-directed learning by providing authentic texts and interactive learning activities based on university students’ needs. The novelty of this study lies in analyzing the needs for developing a web-based application that integrates authentic Arabic news texts and interactive activities for Arabic reading instruction in the context of higher education, an aspect that has not been sufficiently explored in previous studies. This study employed a quantitative descriptive approach at the needs analysis stage of the 4D (Define, Design, Develop, Disseminate) development model. The participants were 20 students from the Arabic Language Education Study Program at Universitas Negeri Malang. Data were collected through a 20-item Guttman-scale questionnaire. The findings revealed that students experienced difficulties in identifying the main idea (90%), understanding new vocabulary (80%), reading unvowelled Arabic texts (70%), and comprehending Arabic texts in general (65%). The results also indicated a high need for additional learning media, flexible access to learning anytime and anywhere (100%), and browser-based applications without installation (90%). All participants also expressed interest in a web-based application containing Arabic news texts and interactive exercises. These findings indicate that developing QiraApp is a relevant innovative learning medium to support Arabic reading instruction at the university level.